Pembinaan Adab Bertetangga terhadap Keharmonisan Masyarakat Berdasarkan Konsep Washiatul Musthofa - Hilyah Ashoumi (Institut Agama Islam Sumatera Barat, 2023)
Based on the observations of the community service team in the village of Pacarpeluk, there is a social gap, namely the lack of harmony between the neighbors of the pacar hamlet and the peluk hamlet. The impact of this disharmony is very influential on the social life of the community. Starting from the lack of mutual cooperation, village activities are very hampered, even conflicts between communities are very vulnerable if this problem has not been resolved. Because there are several impacts that are not expected by the community, the community service team has the initiative to hold a workshop to provide new concepts about how to interact according to Islamic teachings. This community service activity uses a PAR approach which is carried out in a collaborative manner by involving various elements of society in Pacarpeluk Village starting from village government officials, religious leaders, educational practitioners, the majelis ta'alim community, majsid teenagers, youth elements and generally the Pacarpeluk village community. Based on the implementation of PKM activities, it can be concluded that there is a lack of harmony in the community due to the election of the village head where some people disagree with the election of one of the candidates as a result of which there is a social gap between residents. Because of this, the Pacarpeluk village community needs a study where the study aims and functions to understand the community about the importance of neighborly manners and after holding this study the community gets positive results.